(3GdYHQ hOjhGf GdeHJOC hGdNHQ aj CjGe GdYQH hGdYLe hGdHQHQs - (3YHO GdQMef Hf eMeO Hf eMeO, GHf NdOhf CHh RjO, hdqj GdOjf GdMVQeqj GdETHjdj,J (B808 (3g` s
(3ChdgG (B:s
(3ef HOA OhdI Hfi CejI s
(3BNQgG (B:s
(3GdNdaGA GdYHGSjjf HeUQ HYO GfbQGV GdNdGaI HHZOGO s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B330 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B188s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B179 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(4/3042) s
Keywords: (3GdJGQjNs